2002
DOI: 10.1016/s0031-0182(01)00489-8
|View full text |Cite
|
Sign up to set email alerts
|

History of the South Java Current over the past 80 ka

Abstract: A sediment core located below the present South Java Current (SJC) was used to reconstruct paleoclimate and paleoceanography on the basis of biogenic and terrigenic proxy-records. The core spans the past 80 ka of environmental change and shows considerable contrasts from the glacial to the Holocene. Presently, the core site is situated beneath a seasonally varying low-salinity tongue which is advected from the Java Sea via the Sunda Strait. It carries terrigenous matter of a characteristic signature. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…The present limited evidence points to relatively dry conditions, perhaps with the influx of loess, but with no clear indications of episodic local wetness. This provisional reconstruction may again conform with the predictions of greater aridity and marked airflow from the north (Gingele et al 2002;Kershaw et al 2001;Sun et al 2000). There are no clear indications of either greater local wetness or greater moisture stress associated with the relative proximity of the ocean to Niah.…”
Section: Palaeoenvironments and Palaeoclimatesupporting
confidence: 79%
See 2 more Smart Citations
“…The present limited evidence points to relatively dry conditions, perhaps with the influx of loess, but with no clear indications of episodic local wetness. This provisional reconstruction may again conform with the predictions of greater aridity and marked airflow from the north (Gingele et al 2002;Kershaw et al 2001;Sun et al 2000). There are no clear indications of either greater local wetness or greater moisture stress associated with the relative proximity of the ocean to Niah.…”
Section: Palaeoenvironments and Palaeoclimatesupporting
confidence: 79%
“…However, Sun et al (2000) and Kershaw et al (2001) have suggested that northeast Borneo, which would include Niah, might have been notably and consistently wetter than much of the rest of Sundaland during the LGM because of the relative proximity of the ocean and the inferred strengthening of the winter monsoon (Gingele et al 2002). Increased seasonality of climate around Niah during the last glaciation would have resulted.…”
Section: Local and Regional Environments: Present And Pastmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Biogenic and terrigenous proxy records in a core from the northwestern Timor Sea (off South Java), located below the present South Java Current initially indicated that dry conditions with weak monsoonal rainfall and intensified SE trades persisted until B12 ka at that location 21 . However, recent investigations in the same area revealed a more complex pattern with an earlier onset of wet monsoon conditions during the B-A (B15-13 ka), interrupted by a brief period of intensified trade winds and dry conditions during the YD (B13-12 ka) before a second sustained increase from B12 ka onwards 14 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At the Last Glacial Maximum (LGM; 18,000 years ago) the winter monsoon strengthened and the summer monsoon weakened; as a result rainfall over the Sunda Shelf may have been 30%-50% lower than present levels. Temperatures were reduced by as much as 6-7uC, and sea levels withdrew to a maximum of 120 m below current levels Kershaw et al, 2001;Gingele et al, 2002;Bird et al, 2005); however, there is evidence that despite being cooler the climate was not significantly less humid .…”
Section: Paleoclimate and Paleovegetation Of Indochinamentioning
confidence: 99%